A hot mess : how the climate crisis is changing our world - Fleischer, Jeff (Zest Books, 2021)
"Drawing on real-life situations and stories, journalist Jeff Fleischer takes an informed, approachable look at how our world will change as a result of the climate crisis, addressing sea levels, extreme weather, drought, extinction, and migration"--